The Role of Flue Gas Inhibitor on Stabilizing Heptane Flame in Meso Scale Combustor - Achmad Fauzan Hery Soegiharto; Ali Mokhtar; Sudarman; Satworo Adiwidodo (University of Muhammadiyah Malang, 2021)
Mesoscale combustor is one of the components that serves to generate heat on a micro power generator. As one of the components of a micro power generator, meso scale combustor serves to supply heat through the combustion process. The stability of the flame in the combustion chamber meso scale combustor is influenced by the temperature of the combustion chamber. One way to maintain a high temperature in the combustion chamber is to insert a flue gas stainless steel mesh resistor.. This research aims to prove the role of flue gas mesh resistors in stabilizing the flame on the meso scale combustor... The heptane liquid fuel flame was successfully stabilized at an equivalence ratio of ɸ 0.81 – 1.29 and a reactant flow velocity of 26.12 – 36.83 cm/s. The higher the rate of reactant flow, the higher the flame temperature until it reaches 502ºC. Combustor with flue gas mesh resistor is 10 mm away has a flammability limit that is not wider than a combustor without flue gas mesh resistor.